Admissibility Compared: The Reception of Incriminating Expert Evidence (i.e., Forensic Science) in Four Adversarial Jurisdictions - Cole, Simon A. (2014)
There is an epistemic crisis in many areas of forensic science. This crisis emerged largely in response both to the mobilization of a range of academic commentators and critics and the rise and influence of DNA typing. It gained popular and authoritative support through the influence of the National Academy of Science (NAS) and a surprisingly critical report produced under its auspices by a committee of the National Research Council (NRC). Interestingly, as this article endeavors to explain, the courts themselves seem to have played a rather indirect, inconsistent and ultimately ineffective role in the supervision and evaluation of forensic science evidence. Indeed, in the aftermath of recent criticism of the forensic sciences, this essay considers the effect of the dominant admissibility standards that operate in four common law jurisdictions. The revealing result seems to be that although admissibility standards vary across these jurisdictions, actual admissibility practices are remarkably consistent. In this article we will question the extent to which courts (and legal personnel) are able to meaningfully invigilate the use of forensic science evidence in criminal proceedings and consider some of the ideological commitments and institutional pressures that might lead judges in all jurisdictions to prefer inclusive approaches to incriminating expert opinions. In the first part of the article, we compare rules, jurisprudence and practices, across four jurisdictions: the United States, England and Wales, Canada, and Australia. All profoundly shaped by the English common law, these jurisdictions (and their sub- jurisdictions) tend to use a mixture of common law (e.g. England and Wales and Canada), judge-made rules (e.g. the U.S. Federal Rules of Evidence) and statutory schemes (e.g. the Australian Evidence Act 1995 Cth and many states in the United States) to regulate the admission of evidence, including expert opinion. These jurisdictions tend to maintain criminal trial processes that remain reasonably similar and facilitate broad brush comparisons. Our findings suggest that admissibility standards, including the first generation of reliability-based standards, seem to make little, if any, difference to (traditional) admissibility decision-making and practice. Allowing for some variation, the same sorts of forensic science evidence are admitted across all jurisdictions, even where the techniques are not demonstrably reliable and the jurisdiction in question has explicit reliability standards and other rules regulating the admission of expert opinion evidence. Moreover, it is our contention that the legal accommodation of the techniques considered in this article exemplifies a more general response to admissibility and the regulation of forensic science and medicine evidence. In the second part of the article we will consider possible explanations and some of the implications of our findings